A relevância do critério jurídico no auto de infração: análise das modificações e seus limites no curso do processo administrativo brasileiro - Sousa Júnior, Edson Rodrigues de (2023)
The gol of the research is to present the main rules of the Brazilian legal system about the importance of the legal criterion, legal hypotheses of modification and legal limits for changing the progress of the Brazilian administrative process for the infraction notices made by the competent administrative authorities in the exercise of power, review of the tax assessment. These rules are set out in articles 145, 146 and 149 of the National Tax Code of Brazil (CTN). The applied research method is the bibliographical qualitative based on available precedents on the subject. The study will promote understanding of the relevance of the legal criterion in tax assessments and what are the limits for changing the tax assessment in tax assessments (article 146 of the CTN), as well as all the hypotheses described in article 149 of the CTN, in which the assessment can be reviewed ex officio by the administrative authority in the country